A method for preparing perovskite film by regulating the micromorphology of lead iodide layer
During the preparation process of perovskite solar cells, DMF/THTO mixed solvent is used to dissolve lead iodide and the process parameters are optimized to form a lead iodide layer with nanochannels and rich pores, which solves the problem caused by excessive lead iodide residue. The problem of performance degradation has been achieved, and efficient perovskite film preparation and photoelectric conversion efficiency have been improved.
Patent Information
- Application Number
- CN202210139658.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-02-16
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2042-02-16
AI Technical Summary
In the existing two-step method of preparing perovskite solar cells, excessive lead iodide residues lead to degradation of device performance and incomplete reaction.
In the preparation step of the lead iodide layer, the DMF/THTO mixed solvent is used to dissolve the lead iodide, and by optimizing the process parameters, a lead iodide layer with nanochannels perpendicular to the direction of the film and rich pores is formed to facilitate the subsequent two steps. reaction to generate a high-quality perovskite layer.
It effectively improves the photoelectric conversion efficiency of perovskite solar cells, solves the problem of performance degradation caused by excessive lead iodide residue, and enables large-area preparation of high-quality perovskite films.
Smart Images

Figure CN114824102B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solar cells, and in particular relates to a method for preparing a high-performance perovskite film by regulating the microscopic morphology of a lead iodide layer and an application thereof. Background Art
[0002] Solar energy is a clean energy with huge storage capacity. Reasonable use of solar energy is conducive to solving the global energy shortage problem. Solar cells are devices that use photoelectric effect and photochemical effect to directly convert sunlight into electrical energy. They have a wide range of applications and have attracted much attention in recent years. So far, solar cell research mainly includes crystalline silicon solar cells, thin-film solar cells such as gallium arsenide, cadmium telluride and copper indium gallium selenide, as well as dye-sensitized and perovskite solar cells at this stage. They will all be committed to seeking low-cost processes for preparing high-performance devices and applying them to actual production.
[0003] Perovskite solar cells are a rising star among many solar cells. After decades of development, their certified photoelectric conversion efficiency has reached 25.7%. From the perspective of preparation technology, the solution method is the most widely used method for preparing the light-absorbing layer, which meets the expectation of preparing high-performance devices at low cost. However, the current high-performance devices are all based on laboratory-level spin coating and anti-solvent-assisted methods, which are not compatible with large-scale industrial-level production. In the process of preparing large-area thin films by spin coating, performance will be lost to a great extent. Therefore, the realization of large-area preparation of perovskite light-absorbing layers has become a prerequisite for commercializing perovskites.
[0004] The two-step method is currently a relatively easy method for preparing large areas of perovskite films. The main steps include: first depositing an inorganic lead iodide layer, then coating a layer of organic ammonium salt on the lead iodide film, forming a process of mutual reaction and diffusion, and then forming a perovskite film. However, studies have found that the degree of reaction often affects the quality of the film. If there is too much lead iodide residue, the performance of the device will be reduced. Summary of the invention
[0005] The main purpose of the present invention is to provide a method for preparing high-performance perovskite film by improving the morphology of lead iodide, in view of the problems such as incomplete reaction in the existing two-step method for preparing perovskite solar cells, and to introduce a composite solvent containing a THTO additive into the lead iodide layer preparation step and optimize the process parameters to effectively improve the morphology structure of the obtained lead iodide film, so as to form a lead iodide layer with nanochannels perpendicular to the film direction and rich pores, which is beneficial to the subsequent two-step reaction and generates a high-quality perovskite layer, thereby effectively improving the photoelectric conversion efficiency of the obtained perovskite solar cell.
[0006] To achieve the above object, the technical solution adopted by the present invention is:
[0007] A method for preparing a high-performance perovskite film by regulating the microscopic morphology of a lead iodide layer adopts a two-step preparation process, wherein in the first step of preparing the lead iodide film, a DMF / THTO mixed solvent is used to dissolve the lead iodide.
[0008] In the above scheme, the specific preparation method comprises the following steps:
[0009] 1) uniformly dissolving lead iodide powder in a DMF / THTO mixed solvent to obtain a lead iodide solution; dissolving an organic amine in an organic solvent to obtain an organic amine solution;
[0010] 2) depositing the lead iodide solution on the surface of the substrate, performing air blowing-assisted treatment and heating and drying to obtain a lead iodide film;
[0011] 3) The lead iodide film obtained in step 2) is deposited with an organic amine solution under heating conditions (30-150° C. hot base, preferably 50-75° C.) to obtain a black perovskite film, which is then annealed to obtain the high-performance perovskite film.
[0012] In the above scheme, in the DMF / THTO mixed solvent, the volume ratio of DMF to THTO is 9.5: (0.3-0.9); when the THTO content is further increased, it is not conducive to ensuring the continuity between the obtained lead iodide grains, and more THTO will remain in the subsequent perovskite film, affecting the performance of the obtained device.
[0013] In the above scheme, the dosage ratio of the lead iodide powder to the DMF / THTO mixed solvent is 1 g:1.4-10 mL.
[0014] Preferably, the ratio of the lead iodide powder to the DMF / THTO mixed solvent is 1 g: 1.4-2.2 mL.
[0015] In the above scheme, the organic amine can be selected from one or more of formamidine iodide, potassium ammonium chloride, methylammonium iodide and the like.
[0016] Preferably, the organic amine is two or more of formamidine iodide, potassium ammonium chloride, methylammonium iodide and the like.
[0017] Furthermore, in the organic amine, the mass ratio of formamidine iodide to ammonium potassium chloride is 0.1-10:1.
[0018] Preferably, the mass ratio of formamidine iodide to ammonium potassium chloride is 3.7-4.6:1.
[0019] Furthermore, cesium salt may be further introduced into the organic amine solution.
[0020] In the above scheme, the organic solvent in step 1) is an alcohol solvent, and specifically alcohols such as isopropanol and n-butanol can be selected.
[0021] In the above scheme, the concentration of the organic amine solution is 0.01-9.99 mol / L.
[0022] Preferably, the concentration of the organic amine solution is 0.45-0.66 mol / L.
[0023] In the above scheme, in step 2), the lead iodide solution is deposited on the surface of the substrate by coating means; including but not limited to spin coating, scraper coating, spray coating or slit coating.
[0024] In the above scheme, the volume ratio of the lead iodide solution to the organic amine solution is 1:(1.0-5.0).
[0025] Preferably, the volume ratio of the lead iodide solution to the organic amine solution is 1: (1.2-1.8).
[0026] In the above scheme, the coating rate in step 2) is 1-20 mm / s; preferably 1-5 mm / s.
[0027] In the above scheme, the scraping process parameters include: the scraping height is 0.01-1 mm, preferably 0.2-0.5 mm; nitrogen or dry air (air pressure is about 0.3 MPa) is used to blow the film surface.
[0028] In the above scheme, the heating and drying temperature in step 2) is 40-150° C. and the time is 0-30 min.
[0029] Preferably, in step 2), the heating and drying temperature is 50-70° C. and the time is 30-120 seconds.
[0030] In the above scheme, in step 3), the organic amine solution is disposed on the surface of the substrate by coating means, including but not limited to spin coating, scraper coating, spray coating or slit coating.
[0031] In the above scheme, the coating rate in step 3) is 1-20 mm / s; preferably 8-10 mm / s.
[0032] In the above scheme, the annealing treatment temperature in step 3) is 70-150° C. and the time is 0-60 min.
[0033] Preferably, in step 3), the annealing treatment temperature is 130-150° C. and the time is 13-20 min.
[0034] The method for preparing the high-performance perovskite film is applied to prepare a high-efficiency perovskite solar cell, comprising the following steps:
[0035] 1) Etching the transparent conductive substrate and cleaning it for later use;
[0036] 2) depositing an electron transport layer or a hole transport layer on the cleaned transparent conductive substrate;
[0037] 3) Preparation of high-performance perovskite films as perovskite light-absorbing layers (two-step preparation);
[0038] 4) depositing a hole transport layer or an electron transport layer on the surface of the obtained perovskite light absorbing layer;
[0039] 5) Evaporation of metal electrodes.
[0040] In the above solution, the transparent conductive substrate can be FTO, ITO, etc.
[0041] In the above scheme, the electron transport layer can be made of tin dioxide, titanium dioxide, zinc oxide, PCBM, C60, etc.; the hole transport layer can be made of Spiro-OMeTAD, PTAA, P3HT, nickel oxide, etc.
[0042] In the above solution, the metal electrode can be made of gold or silver.
[0043] In the above scheme, the two-step method for preparing the light absorbing layer includes but is not limited to: spin coating, blade coating, spray coating, slit coating or any combination of processes, etc.
[0044] In the above scheme, the perovskite solar cell structure includes but is not limited to: nip formal and pin trans structures.
[0045] The principle of the present invention is:
[0046] In the two-step preparation process of organic-inorganic hybrid perovskite of the present invention, a DMF / THTO mixed solvent is firstly used to dissolve lead iodide powder, so as to effectively control the microscopic morphology of the deposited lead iodide layer and promote the reduction of the film drying temperature, thereby promoting the lead iodide to form nanochannels and abundant pore structures perpendicular to the film direction during the film formation process, which provides a wider reaction area for subsequent organic ammonium salt ions, promotes complete reaction and effectively improves the perovskite film formation quality.
[0047] Compared with the prior art, the present invention has the following beneficial effects:
[0048] 1) The present invention proposes for the first time to use a DMF / THTO mixed solvent to dissolve lead iodide, and by optimizing the deposition conditions, improves the morphology and structure of the resulting lead iodide film, which is beneficial to the subsequent two-step reaction (organic amine diffusion reaction) to generate a high-quality perovskite layer; effectively solving the problem of incomplete reaction in the traditional two-step preparation process;
[0049] 2) The preparation method involved in the present invention is relatively simple, easy to operate, and has low energy consumption. The two-step method adopted is also an important preparation process for achieving large-area high-quality perovskite films, and is suitable for promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] Figure 1 It is a schematic diagram of the principle of introducing different additives (Example 1 and Comparative Example 1) by a two-step scraping method.
[0051] Figure 2 This is a SEM image of the lead iodide film obtained in step 2) of Example 1;
[0052] Figure 3 a is a diagram of the photoelectric conversion efficiency of the perovskite solar cell obtained in comparative example 1, Figure 3 b is a diagram of the photoelectric conversion efficiency of the perovskite solar cell obtained in Example 1;
[0053] Figure 4 This is a SEM image of the lead iodide film obtained in step 2) of comparative example 1. DETAILED DESCRIPTION
[0054] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with specific embodiments, but the content of the present invention is not limited to the following embodiments.
[0055] Example 1
[0056] A method for preparing a perovskite solar cell, using a DMF / THTO mixed solvent in the process of dissolving lead iodide powder, the principle schematic diagram is shown in Figure 1 , the specific steps are as follows:
[0057] 1) Preparation of transparent conductive substrate: 10cm×10cm×2.2mm FTO conductive glass was etched by femtosecond or nanosecond laser, with laser power of 20W and etching depth of about 670nm. Then the etched glass was ultrasonically cleaned in cleaning solution (detergent solution), pure water and ethanol for 20 min respectively, and then dried with an air gun for later use;
[0058] 2) Deposition of SnO2 electron transport layer: 5 g urea, 5 mL concentrated hydrochloric acid (37.5wt%), 100 μL thioglycolic acid and 1.096 g SnCl2·2H2O were added to 400 mL deionized water (ice water) in sequence and evenly dispersed and placed in a refrigerator for later use; 20 mL of the obtained SnCl2 solution was diluted 6 times and poured into a glass container; the cleaned conductive substrate was then UV treated for 15 min and immersed in the obtained SnCl2 dilution, and the glass container was placed in a 90℃ oven for 2.5 h for chemical bath deposition; after the reaction was completed, it was rinsed with pure water, and ultrasonicated in pure water and isopropanol for 3 min in sequence, dried with nitrogen, and annealed at 180℃ for 1 h to obtain a dense and uniform SnO2 electron transport layer on the surface of the conductive substrate;
[0059] 3) Preparation of perovskite light-absorbing layer (method for preparing high-performance perovskite film by regulating the microscopic morphology of lead iodide layer):
[0060] Prepare the lead iodide precursor solution: weigh 600 mg of lead iodide powder, dissolve it in 1 mL of DMF / THTO (tetramethylene sulfoxide) mixed solvent (volume ratio is 9.5:0.5), and then place it in an oscillator to fully dissolve it for later use;
[0061] Prepare organic ammonium salt solution: dissolve 60 mg FAI and 15 mg MACl in 1 mL IPA (isopropanol), and then place in an oscillator to fully dissolve for later use;
[0062] Scrape coating lead iodide film: Cut the substrate with SnO2 electron layer deposited in step 2) into 5 cm × 5 cm size and place it on the coating table. Adjust the height between the scraper head and the substrate to about 0.48 mm. Take 60 μL of the prepared lead iodide precursor solution and place it on the blade head, forming a concave liquid surface between the blade head and the substrate. Adjust the coating speed to 4 mm / s. After scraping, take out the glass substrate, use an air gun to blow dry, and then place it on a 70°C hot stage for drying for 1 min to form a yellow lead iodide film.
[0063] Scrape coating of organic ammonium salt: Place the obtained glass substrate with lead iodide film on a 50 ℃ substrate, adjust the height between the scraper head and the substrate to about 0.56 mm, take 80 μL of the prepared organic ammonium salt solution and place it between the blade and the substrate, and the coating speed is 8 mm / s. After scraping, a black perovskite film is obtained, and then placed on a hot stage for annealing at 150 ℃ for 15 min to obtain a perovskite light-absorbing layer;
[0064] 4) Preparation of Spiro-OMeTAD hole transport layer: 91.4 mg of Spiro-OMeTAD powder was dissolved in 1 mL of chlorobenzene, and then 35.65 μL of tert-butylpyridine, 21 μL of 520 mg / mL Li-TFSI / acetonitrile solution and 15 μL of 300 mg / mL FK209 / acetonitrile solution were added. After mixing, the mixture was placed on an oscillator for even shaking. An appropriate amount of the obtained Spiro-OMeTAD solution was dropped on the surface of the annealed perovskite film, and the spin coating speed was 4000 rpm. The hole transport layer was prepared for 20 s.
[0065] 5) Evaporation of metal electrode: The product obtained in step 4) is placed in an evaporator under high vacuum (2.5×10 -4 A gold electrode with a thickness of 80 nm is evaporated at a stable rate of 1.5 Å / s to obtain the perovskite solar cell.
[0066] The lead iodide film (cross section) obtained in step 3) of this embodiment was analyzed by scanning electron microscopy, and the results are shown in FIG. Figure 2 It can be seen that nanochannels perpendicular to the film direction can be formed in the obtained lead iodide film, and rich pore structures can be formed at the same time.
[0067] The perovskite solar cell obtained in this example was tested for photoelectric conversion efficiency. Under a solar simulator and standard one sun, the test mask area was 0.16 cm 2 , scanning speed 10 mV / s, through the forward and reverse scanning test IV The results show that the reverse sweep power conversion efficiency of the device prepared with THTO as an additive can reach 22.21% (see Figure 3 b).
[0068] Comparative Example 1
[0069] A method for preparing a conventional perovskite solar cell (see the principle) Figure 1 ), the preparation method is substantially the same as that of Comparative Example 1, except that, in the process of dissolving the lead iodide powder, traditional DMSO is used to replace the THTO described in Example 1, and the preparation steps of the lead iodide precursor solution are specifically as follows: 600 mg of lead iodide powder is weighed, dissolved in 1 mL of DMF / DMSO mixed solvent (volume ratio of 9.5:0.5), and then placed in an oscillator to fully dissolve for later use.
[0070] The lead iodide film (cross section) obtained in step 3) of this comparative example was analyzed by scanning electron microscopy, and the results are shown in FIG. Figure 4 , it can be observed that the formed lead iodide grains are small and densely stacked (containing only a small amount of voids), and are arranged as a whole in the direction parallel to the film, which is not conducive to the subsequent organic ammonium salt penetration reaction.
[0071] The photoelectric conversion efficiency of the perovskite solar cell obtained in this comparative example was tested under a solar simulator with a standard one-sun light. The test mask area was 0.16 cm 2 , scanning speed 10 mV / s, through the forward and reverse scanning test I - V The results show that the reverse sweep power conversion efficiency of the device prepared with DMSO as an additive is 20.03% (see Figure 3 a).
[0072] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a perovskite film by regulating the microscopic morphology of a lead iodide layer, characterized in that: The specific preparation method comprises the following steps: 1) uniformly dissolving lead iodide powder in a DMF / THTO mixed solvent to obtain a lead iodide solution; dissolving an organic amine in an organic solvent to obtain an organic amine solution; 2) depositing the lead iodide solution on the surface of the substrate, blowing it dry, and then heating and drying it to obtain a lead iodide film; a nanochannel perpendicular to the film direction is formed in the obtained lead iodide film, and a pore structure is formed at the same time; 3) depositing an organic amine solution on the lead iodide film obtained in step 2) under heating conditions to obtain a black perovskite film, and then performing annealing treatment to obtain the perovskite film; The volume ratio of DMF to THTO in the DMF / THTO mixed solvent is 9.5:(0.3-0.9).
2. The method according to claim 1, characterized in that The dosage ratio of the lead iodide powder to the DMF / THTO mixed solvent is 1 g:1.4-10 mL; the volume ratio of the lead iodide solution to the organic amine solution is 1:(1.0-5.0).
3. The method according to claim 1, characterized in that The organic amine can be one or more of formamidine iodide, methylammonium chloride and methylammonium iodide; and the organic solvent is an alcohol solvent.
4. The method according to claim 1, characterized in that: The concentration of the organic amine solution is 0.01-1 mol / L.
5. The method according to claim 1, characterized in that Step 2) The heating and drying temperature is 40-150°C and the time is 0-30 minutes.
6. The method according to claim 1, characterized in that Step 3) The annealing temperature is 100-150°C and the time is 0-30 min.
7. A method for preparing a perovskite solar cell using the perovskite film obtained by the method according to any one of claims 1 to 6, characterized in that: The steps include: 1) Etching the transparent conductive substrate and cleaning it for later use; 2) depositing an electron transport layer or a hole transport layer on the cleaned transparent conductive substrate; 3) Prepare perovskite film to obtain perovskite light absorbing layer; 4) depositing a hole transport layer or an electron transport layer on the surface of the obtained perovskite light absorbing layer; 5) Evaporation of metal electrodes.
8. The method according to claim 7, characterized in that The electron transport layer includes but is not limited to tin dioxide, titanium dioxide, zinc oxide, PCBM or C60; the hole transport layer includes but is not limited to Spiro-OMeTAD, PTAA, P3HT or nickel oxide.